Simulation of transient heat transfer during forced convection cooling of cocoyam (Colocasia Esculenta (L.) Schott) tubers. Issue 12 (December 2022) - Ndisya, John; Gitau, Ayub; Roman, Franz; Mbuge, Duncan; Sturm, Barbara; Hensel, Oliver
Abstract: In this study, a prediction model based on transient heat transfer was modified and validated using experimental data. The time required to cool tubers from field temperature of 30 ± 2 °C to the target storage temperature of 12 ± 0.2 °C was predicted directly from the model. Moreover, total cooling time ranged from 127.8 – 154.2 min for small tubers and 190.8–262.2 min for large tubers while the field heat removed ranged from 9.61 – 10.17 kJ for small tubers and 24.78–31.90 kJ for large tubers between the extremes of the air velocity. Tuber orientation to airflow neither influenced the heat transfer coefficients and Biot numbers nor the cooling time and amount of field heat removed. The results from this study could be applied in the design and optimisation of forced convection cooling systems to precool tubers immediately after harvest and for extended duration storage. Abstract : Field heat removal; Forced convection precooling; Transient heat transfer; Postharvest storage.